2019
DOI: 10.1021/acs.inorgchem.9b01126
|View full text |Cite
|
Sign up to set email alerts
|

Hydroboration of Alkynes: η4-Alkene–Borane versus η4-E-Boratabutadiene

Abstract: A series of hydroborated η4-σ,π-alkene–borane complexes have been synthesized from the reaction of ruthenium–bis­(σ)­borate complex [Cp*Ru­(μ-H)2BH­(S-CHS)] (1) and terminal as well as internal alkynes. Likewise, the reactions of manganese–bis­(σ)­borate complexes [Mn­(CO)3(μ-H)2BHNCSC6H4(NL)] (L = NCSC6H4 or H) were explored with terminal alkynes that yielded boratabutadiene complexes [Mn­(CO)3{(NCSC6H4)2N}­{(R1MeC)B­(HCCHR1)}] [R1 = phenyl (4a) or p-tolyl (4b)] via triple hydroboration of alkynes. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…1a The availability of Mn bis(σ)-borate complexes, [(OC) 3 Mn(H) 2 BHL] 13 (L = bbza (5a) or abz (5b), bbza = N(NCSC 6 H 4 ) 2 , abz = HN 2 CSC 6 H 4 ) allowed the investigation of their reactivity with different types of alkynes (Scheme 4). 14 As Scheme 3 Intramolecular hydroboration of Mo-borate complexes, 3a-3b. The reaction of 5a with diphenylacetylene produced [{(Ph) HCvC(Ph)B}(H) 2 (bbza)Mn(CO) 3 ], 6c.…”
Section: Hydroboration Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…1a The availability of Mn bis(σ)-borate complexes, [(OC) 3 Mn(H) 2 BHL] 13 (L = bbza (5a) or abz (5b), bbza = N(NCSC 6 H 4 ) 2 , abz = HN 2 CSC 6 H 4 ) allowed the investigation of their reactivity with different types of alkynes (Scheme 4). 14 As Scheme 3 Intramolecular hydroboration of Mo-borate complexes, 3a-3b. The reaction of 5a with diphenylacetylene produced [{(Ph) HCvC(Ph)B}(H) 2 (bbza)Mn(CO) 3 ], 6c.…”
Section: Hydroboration Reactionsmentioning
confidence: 99%
“…In order to understand the role of the ligand associated with the transition metal borane/borate complexes in the hydroboration of alkynes, the reactivity of bis(σ)-borane complex 23 [Cp*Ru(μ-H) 2 BH(SvCHS)], 14, was investigated with different alkynes. 14 The thermolysis of 14 with [R 4 CuCR 5 ] yielded the alkeneborane complexes [Cp*Ru(SvCHS)(H)BH {R 4 CvCHR 5 }], 15a-15g [R 4 = H; R 5 = Ph (15a), p-tol (15c), CO 2 Me (15e); R 4 = H; R 5 = Ph (15b), p-tol (15d), CO 2 Me (15f ); R 4 = R 5 = CO 2 Me (15g)] (Scheme 6c). 14 Although complexes 15a-15b and 15c-15d were obtained as inseparable mixtures, 15e and 15f were isolated in their pure form.…”
Section: Dalton Transactions Frontiermentioning
confidence: 99%
See 1 more Smart Citation
“…70 4). 2,71,73,74,76 These alkenylboranes are believed to be the intermediates in the formation of vinylborane species. The solid-state structure of 41b confirmed that the hydroboration of the alkyne occurred via Markovnikov addition in which the olefinic unit (MeO 2 C−CCH 2 ) is coordinated to the Ru center in an η 2 fashion (Figure 8a).…”
Section: Hydroboration Reactionsmentioning
confidence: 99%
“…Alkenylborane complex 44c, generated from the reaction of ethynylmagnesium bromide and 43, features an η 4σ,π-ethyleneborane unit. Similarly, reaction of the bis(σ)-borate complex [Cp*Ru(μ-H) 2 BH{SC(H)S}] 75 (47) and phenylacetylene yielded the η 4 -σ,π-alkenylborane complexes [Cp*Ru-(μ-H)B(H)(RCCHR′)(CS 2 H)] (R = H, R′ = Ph (48a); R = Ph, R′ = H (48b); Table4and Figure9) 76. Photolysisof 25 with p-TolCCH at room temperature yielded [(OC) 3 Mn{(p-Tol)C(H)C(H)−BC(Me)(p-Tol)}(NC(NR 1 )SC 6 H 4 )] 76 (49) (R 1 = C 7 H 4 NS; Scheme 15) having a 11 B{ 1 H} NMR resonance at 25.7 ppm, which is deshielded relative to that of 25 (13.4 ppm).…”
mentioning
confidence: 99%